The Scion/Rootstock Genotypes and Habitats Affect Arbuscular Mycorrhizal Fungal Community in Citrus - Song, Fang; Pan, Zhiyong; Bai, Fuxi; An, Jianyong; Liu, Jihong; Guo, Wenwu; Bisseling, Ton; Deng, Xiuxin; Xiao, Shunyuan (Frontiers in Microbiology, 2015)
Citrus roots have rare root hairs and thus heavily depend on arbuscular mycorrhizal fungi (AMF) for mineral nutrient uptake. However, the AMF community structure of citrus is largely unknown. By using 454-pyrosequencing of 18S rRNA gene fragment, we investigated the genetic diversity of AMF colonizing citrus roots, and evaluated the impact of habitats and rootstock & scion genotypes on the AMF community structure. Over 740,000 effective sequences were obtained from 77 citrus root samples. These sequences were assigned to 75 AMF virtual taxa, of which 66 belong to Glomus, highlighting an absolute dominance of this AMF genus in symbiosis with citrus roots. The citrus AMF community structure is significantly affected by habitats and host genotypes. Interestingly, our data suggests that the genotype of the scion exerts a greater impact on the AMF community structure than that of the rootstock where the physical root-AMF association occurs. This study not only provides a comprehensive assessment for the community composition of the AMF in citrus roots under different conditions, but also sheds novel insights into how the AMF community might be indirectly influenced by the spatially separated yet metabolically connected partner – the scion – of the grafted citrus tree.